Performances : Happenings, Actions, Events, Activities, Installations... - Inga-Pin, Luciano (Padova : Mastrogiacomo Editore, 1978)
Abramovic, Marina ; Abramovic, Marina & Ulay ; Acconci, Vito ; Anderson, Laurie ; Ant Farm ; Antin, Eleanor ; Ball, Hugo ; Barbara, Joan La ; Bertlmann, Renate ; Beuys, Joseph ; Bianco, Remo ; Bonito Oliva, Achille ; Bozzolla, Angelo ; Brown, Robert Delford ; Brown, Trisha ; Brus, Günter ; Burden, Chris ; Buthe, Michael ; Calzolari, Pierpaolo ; Cameron, Shirley ; Caminati, Aurelio ; Carpi, Cioni ; Castelli, Luciano ; Cavellini, G.A. ; Chaimowicz, Marc Camille ; Charlier, Jacques ; Chia, Sandro ; Chiari, Giuseppe ; Christanell, Linda ; Christo ; Clark, Lygia ; Collins, James ; Coppelo, Francisco ; Coum Transmissions ; Croce, Giancarlo ; d'Armagnac, Ben ; Damnyan, Radomir ; Depero, Fortunato ; Desiato, Giuseppe ; de Dominicis, Gino ; Duchamp, Marcel ; Eiag ; English, Rose ; Export, Valie ; Fabro, Luciano ; Filippini, Alessandro ; Fioroni, Giosetta ; Foreman, Richard ; Forti, Simone ; Fox, Terry ; Fraizer, C. ; General Idea ; Gerstein, M. ; Gilbert & George ; Gretta ; Gruppo 70 ; Hay, Alex ; Hay, Deborah ; Hendricks, Geoffrey ; Heyward, Julia ; Hoover, Nan ; Horn, Rebecca ; Job, Enrico ; Johnson, Poppy ; Jonas, Joan ; Journiac, Michel ; Kagel, Mauricio ; Kaprow, Allan ; Klein, Yves ; Knowles, Alison ; Koncert Morski ; Kosuth, Joseph ; Kounellis, Jannis ; de Kroon, Harrie ; Krzyzanowski, Michel Szulc ; Kubisch, Christina ; Kudo, Tetsumi ; Kusama Yayoi ; Lebel, Jean Jacques ; Leisgen, Barbara & Michael ; Lind, Pi ; LL, Natalia ; Lloyd, Barbara ; Lüthi, Urs ; Magro, Giovanna dal ; Mainolfi, Luigi ; Malasch, Robert ; Man Ray ; Maniac Productions ; Manon ; Manzoni, Piero ; Marocco, Armando ; Marroquin, Raoul ; Martelli, Plinio ; Mathieu, Georges ; Mattiacci, Eliseo ; Mauri, Fabio ; Mazzuchelli, Franco ; Messager, Annette ; Michals, Duane ; Miller, Roland ; etc.
Italiaans
boek